2015
DOI: 10.1111/1471-0528.13805
|View full text |Cite
|
Sign up to set email alerts
|

Elective induction of labour and maternal request: a national population‐based study

Abstract: About 13.9% of inductions of labour were elective in France, 47.3% of these requested by women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In accordance with other studies, the main factor associated with elective induction compared to medically indicated induction was parity, with a markedly higher rate of multiparous women in the elective group [5, 8, 12, 13]. A substantial amount of elective inductions in the present study was due to a negative delivery experience and/or obstetric history.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In accordance with other studies, the main factor associated with elective induction compared to medically indicated induction was parity, with a markedly higher rate of multiparous women in the elective group [5, 8, 12, 13]. A substantial amount of elective inductions in the present study was due to a negative delivery experience and/or obstetric history.…”
Section: Discussionsupporting
confidence: 90%
“…In the USA, 16% of term deliveries were induced without medical indication [9]. Coulm et al found that 13.9% of the induced labors were elective in France [5]. Even if the rate of elective inductions in Norway seem to be slightly lower than in other western countries, the increase in elective inductions is still of concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American College of Obstetricians and Gynaecologists too have not recommended elective induction for non obstetric reasons 8 . In a recent large multi center study involving more than 3000 women, carried out in the USA, Induction of labour at 39 weeks in low-risk nulliparous women resulted in a significantly lower frequency of caesarean delivery (CD) although it did not result in a significantly lower frequency of a composite adverse perinatal outcome In a population based study carried out in France in 2010, involving about 14,680 women, there were about 13.9% of elective IOL and 47.3% of them were on the request of the women 10 . Therefore it has been suggested that even in the UK, elective IOL at term on maternal request should be an option which should be available to women 11 , although the NICE Guidelines do not recommend this 14 .…”
mentioning
confidence: 99%